Development of Data-Driven Educational Decision Implementation Guidelines Assisted by Formative Tests in Science Learning - Suwito Singgih; Agista Sintia Dewi Adila; Ismun Nisa Nadhifah; Syakira Alfi Kurnia; Aza Mazita (AL-ISHLAH: Jurnal Pendidikan, 2024)
Data-Based Educational Decisions (DDED) is an important part of the learning process where DDED is used to improve the quality of learning. This research purpose to develop Data Driven Educational Decision Implementation Guidelines (DDED) supporting formative tests in IPA learning. DDED is an adaptation of Data Drive Decision Making (DDDM) in learning. DDED is based on Data Drive Decision Making (DDDM), which is a decision-making process that has been widely applied in the world of management. The DDED directs teachers to be adaptive and flexible in implementing various methods, models, teaching materials and learning media based on student access. The development design used is 4D which consists of defining, designing, developing and deploying. The content of the guidelines has been agreed through expert consensus through the fuzzy delphi technique. Fuzzy Delphi Method to create a broad and detailed understanding, especially in education.   The consensus indicated that formative tests should include relevant questions and quizzes, comprising both multiple-choice and essay formats, aligning with the principles of DDED. The resulting guideline tests the level of validity and user response. Users respond well to the guidelines developed.